Maternal Periodontitis and Low Birth Weight Babies - Vanka, Shanthi; Saxena, Vrinda; Vanka, Amit; Ravi, KS (Journal of Orofacial Research, 2013)
Introduction: Low birth weight in developing countries is primarily because of poor maternal health and nutrition. If maternal health plays such an important role in the child’s development, all the means of preventing problems among the pregnant women is of utmost importance. Aim: This study was conducted to assess the relationship between maternal periodontitis and the weight of the baby after birth. Materials and methods: The subjects in the present longitudinalstudy were chosen from the outpatients of Gynecology Department of the People’s Hospital over a period of 1 month. The periodontal status was assessed based on community periodontal index (CPI) and loss of attachment (LOA). Results: All the participants demonstrated periodontal pockets with more than half the population (56%) presenting shallow pockets (pockets of 4-5 mm). Conclusion: In the present study, periodontal status of the mother was significantly related to delivery of low birth weight babies. Thus it can be concluded that periodontitis may be associated with delivery of low birth weight babies.